The Seductive Computer Why IT Systems Always Fail - Partridge, Derek (Springer London : Imprint: Springer, 2011)
IT systems explode budget estimates, bust production deadlines by years, and then fail to work properly. Why this IT-system crisis? Poor programmers? Inadequate project management? No.  The Seductive Computer argues that the fundamental nature of programming technology itself is the real culprit; it promises perfection but can only deliver emergent chaos. It is also an insidiously compelling technology, peculiarly male oriented.  IT systems, an unavoidable and increasing reality in all our lives, are something new to man - large-scale discrete complexity. The Seductive Computer explains this novelty that defies human understanding.  This book illustrates in a simple yet thorough manner the underlying concepts necessary for understanding the IT-system crisis - not 'How To Program' but what the demands of programming are. It then proceeds to lay out the full gamut of issues - all stemming from the nature of the technology.  From development to maintenance IT-system personnel are grappling with incipient chaos. The technicians are seduced by the detailed challenge of the technology. The scientists are seduced by the promises of their technology. The managers and users are seduced by the mysteries of the technology. No IT system is ever fully understood by anyone, so surprising behaviours will always emerge.  What can be done? We must rein in our expectations of IT systems: what they can do, and how reliably they can do it. On the positive side, The Seductive Computer discusses novel paradigms that look beyond the current discrete technology: neural computing and precise approximation computing.